DARI ISOLASI KE SOLIDARITAS: PERAN PARENTAL SUPPORT GROUP DALAM PENERIMAAN DIRI ORANG TUA ANAK DIFABEL - Tatum Tivani; Ferra Puspito Sari; Arya Fendha Ibnu Shina; Nailul Falah (UIN Sunan Kalijaga Yogyakarta, 2026)
This study explores how parental support groups facilitate the acceptance process among parents of children with disabilities. A mixed-methods approach was employed, integrating quantitative comparison using the Wilcoxon Signed-Rank Test with an Interpretative Phenomenological Analysis (IPA). Data were collected through a self-acceptance questionnaire and in-depth interviews with five parents who had actively participated for at least six months, and limited observations during group meetings. The findings indicated a significant improvement in parental self-acceptance after joining the support group (Wilcoxon Signed-Rank Test, p = .041). Qualitative findings revealed that acceptance developed as a relational process characterized by reduced social isolation, emotional normalization, and an increased sense of belonging. The support group functioned as a collective safe haven that provided emotional security and as a secure base that fostered parents' identity transformation, enabling them to become more confident, proactive, and empowered. Parents also reconstructed their perceptions of themselves, their children, and family life. Nevertheless, acceptance remained dynamic and was continually challenged by social stigma, caregiving burden, and concerns about the future. These findings underscore the importance of developing community-based Islamic guidance and counseling grounded in the values of ta'awun, sabr, ikhtiar, and tawakkal to strengthen parental resilience and acceptance. Keywords: parental support group, parental acceptance, children with disabilities